Understanding the earth system : global change science for application - Cornell, Sarah, 1969-; Prentice, I. Colin, 1952-; House, Joanna; Downy, Catherine (Cambridge : Cambridge University Press, 2012)
'Explaining the what, the how and the why of climate science, this multidisciplinary new book provides a review of research from the last decade, illustrated with cutting-edge data and observations. A key focus is the development of analysis tools that can be used to demonstrate options for mitigating and adapting to increasing climate risks. Emphasis is given to the importance of Earth system feedback mechanisms and the role of the biosphere. The book explains advances in modelling, process understanding and observations, and the development of consistent and coherent studies of past, present and'possible' climates. This highly-illustrated, data-rich book is written by leading scientists involved in QUEST, a major UK-led research programme. It forms a concise and up-to-date reference for academic researchers or students in the fields of climatology, Earth system science and ecology, and also a vital resource for professionals and policymakers working on any aspect of global change'--
Includes bibliographical references and index.
Keywords: Dynamic climatology; Dynamic meteorology